2022
DOI: 10.1027/2157-3891/a000049
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19-Associated Discrimination on Anxiety and Depression Symptoms in Asian American Adolescents

Abstract: Abstract. Given the potential adverse impact of COVID-19-associated discrimination (CAD) targeting Asian Americans, we investigated the relationship between online and in-person CAD and mental health outcomes in a sample of East and Southeast Asian American (ESEAA) high school students ( n = 114). The study findings revealed that students with experiences of CAD in online and offline settings reported higher levels of anxiety and depression symptoms above and beyond the traumatic events and lifetime discrimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Based on a sample of East and Southeast Asian American high school students, in the second article, Ermis-Demirtas et al (2022) investigated the relationship between mental health outcomes and online and in-person COVID-19–associated discrimination. The results indicated that students with experiences of online and offline discrimination reported greater levels of symptoms of depression and anxiety beyond the traumatic events and other discrimination they had faced in their lives.…”
mentioning
confidence: 99%
“…Based on a sample of East and Southeast Asian American high school students, in the second article, Ermis-Demirtas et al (2022) investigated the relationship between mental health outcomes and online and in-person COVID-19–associated discrimination. The results indicated that students with experiences of online and offline discrimination reported greater levels of symptoms of depression and anxiety beyond the traumatic events and other discrimination they had faced in their lives.…”
mentioning
confidence: 99%
“…In addition to experiencing many of their formative schooling years online, due to pandemic safety precautions, Asian American adolescents and young adults' intentional avoidance of public spaces for fear of racial violence can come at the cost of sustaining social connection to support systems and having a sense of belonging in their neighborhoods, all of which may have long-term mental health consequences across the life course (45). Specifically, these experiences of isolation and anti-Asian racism may contribute to Asian American adolescents' developmental trajectory, which may be in more flux than young adults, such that it increases fear and mistrust of others, promoting intergroup hostility, concealing one's culture, and hinder positive identity development (12,(16)(17)(18). Furthermore, our results on depression severity by gender, highlight and endorse the gendered disparities in mental health and experiences of violence (46).…”
Section: Table Distribution Of Perceptions Of Safety and Anti-asian V...mentioning
confidence: 99%
“…Adolescence is a stage of rapid physical, social, and brain development; thus, AA adolescents and young adults may be especially vulnerable to increased depressive symptoms due to their exposure to multiple stressors associated with the COVID-19 pandemic, such as increased social isolation, family financial strain, and increased social media use. They also feared for their own safety as they became direct targets of anti-Asian hate crimes (12,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Within the study sample, Asian and Black adolescents endorsed the highest levels of perceived racism and/or worrying about confronting racism over the pandemic [ 36 ]. Additional studies with Asian adolescent samples demonstrated associations between discrimination exposure during the pandemic and poor mental health (e.g., depression, post-traumatic stress symptoms) [ 37 , 38 ].…”
Section: Variation In the Impacts Of The Pandemic For Well-beingmentioning
confidence: 99%